Co-initiating-system dual-mechanism drives the design of printable entangled polymer multinetworks - An Wei; Qian Wang; Jupen Liu; Yuchan Huang; Haoxiang Li; Zhenhao Zhu; Tao Wang; You Yu (Nature Communications)
Abstract Entanglement significantly enhances the mechanical performance and functionality of both natural and synthetic materials. However, developing straightforward, versatile strategies for creating high-performance entangled polymer materials remains a challenge. Here, a co-initiating-system dual-mechanism strategy is designed for fabricating printable entangled polymer multinetworks. This thermal-light dual-initiation process benefits the synthesis of high-molecular-weight polymers and promotes the rapid formation of multinetworks within hydrogels. The resulting long polymer chains enable hydrogels with higher mechanical performance, lower stress relaxation, and activation energy compared to short polymer chain-contained samples. Such a method proves more effective than traditional self-thickening and strengthening techniques for enhancing hydrogel entanglements and is also compatible with additive manufacturing, enabling the design of complex 2D webs with adaptive mechanical performance and capable of detecting and sensing applications. This work provides an effective strategy for designing high-performance entangled polymer materials, which are set to impact numerous fields, from advanced sensing to material science and beyond.